Experimental and Numerical Investigations of Punching Shear Strengthening of Slab-Circular Column Connection Incorporating UHPC and Galvanized Threaded Steel Bolts - Ahmed Hamoda; Khaled Sennah; Mizan Ahmed; Aref A. Abadel; Mohamed Emara (International Journal of Concrete Structures and Materials)
Abstract Punching shear failure poses a critical risk in flat slab–column structures, potentially leading to catastrophic collapses. Retrofitting methods typically involve flexural or shear strengthening. Recent studies, however, reveal that combining indirect flexural strengthening with direct shear strengthening augments the punching shear performance. This research employed ultra-high-performance engineered cementitious composites (UHP-ECC) and ultra-high-performance steel-fiber-reinforced concrete (UHP-SFRC) as a bonded layer on the slab’s compression zone confining column as indirect flexural strengthening and galvanized threaded steel bolts as direct shear strengthening through slab thickness to augment the punching shear capacity. Six square flat slabs with central circular columns were constructed and then experimented to collapse to verify the effect of this proposed strengthening technique. The effects of various mesh and concrete types are investigated. Results showed that combining the UHP-ECC or UHP-SFRC bonded layer in the compression side with bonded galvanized threaded steel bolts significantly enhanced the punching shear strength of the slabs. The experimental findings demonstrated a remarkable increase of 62% and 111% over the unstrengthened slab for the UHP-ECC and UHP-SFRC strengthened slabs with single-layer mesh, respectively. Further enhancements were observed by adding a second steel reinforcement mesh to the UHP-bonded layer. A numerical model was developed using the finite-element (FEM) method to predict the structural behavior of tested slabs. Numerical results revealed that the FEM predicts well the performance of the slab–column connection, aligning well with experimental findings.